Protoberberine alkaloids isolated of Guatteria schomburgkiana (G. sessilis) - Rodríguez, María; Bastidas, Elsy; Hasegawa, Masahisa (Ciencia, 2011)
From the leaves of Guatteria schomburgkiana Mart. (Guatteria sessilis R.E. Fries), three protoberberine alkaloids: anisocycline, lincangenine and palmatine, and one tetrahydroprotoberberine thaicanine, has been isolated. For our knowledge, this is the first report of these alkaloids in the Guatteria genus. The structures were established by spectroscopic methods, including previously unreported13C-NMR and Mass spectral data for anisocycline.